THE RESPONSIBILITY TO PROTECT (R2P): PROJECT BEAUTY AND THE QUEST FOR GENDER SECURITY OF CHINESE UYGHUR IN XINJIANG - Satria Rizaldi Alchatib; Ellen Monica Audrey Suharyanto (Indonesian Journal of International Relations, 2022)
Abstract While discourse on minority prosecution has been on the spotlights for quite some years, gender-based violence towards the Uyghur women has been lacks of addresses in international research and policy responses. The Government of China continual negligence and ‘perceived immunity’ from international sanction had ‘sidelined’ the deliberation of various human-rights norms, including and particularly, the Responsibility to Protect (R2P), resulting various incidents of gender-based violence in the state of Xinjiang. Based on this premise, this paper seeks to address the omission by reconceptualizing gender security in the context of Uyghur women as a double minority who experienced a structural deconstruction of identity and existence as a consequence of the state-led ‘Project Beauty’ initiative. In addition to this, there has been a lack of reference to the terminology of the Responsibility to Protect (R2P) relative to the gender-based violence in general. Therefore, using the context of Uyghur women, this paper aims at investigating the normative force of the Responsibility to Protect (R2P) and to seek whether the neglect of R2P indicative with large-scale human rights violations as displayed against the Uyghur women. Keywords: Responsibility to Protect (R2P); Gender Security; Human Rights; Uyghur Women Abstrak Diskursus mengenai persekusi minoritas yang dilakukan oleh Pemerintah Cina telah menjadi sorotan selama berdekade, namun isu kekerasan berbasis gender terhadap perempuan Uyghur sangat kurang teriset dalam disiplin hubungan internasional dan kebijakan luar negeri. Kelalaian Pemerintah Cina dan 'kekebalan’ nya terhadap sanksi internasional telah mendelegitimasi berbagai norma HAM internasional, khususnya Resonsibility to Protect (R2P) yang menyebabkan terjadinya berbagai insiden kekerasan berbasis gender di negara bagian Xinjiang. Berdasarkan premis tersebut, artikel ini berusaha untuk menelaah gap tersebut dengan merekonseptualisasikan keamanan gender dalam konteks wanita Uyghur sebagai double minority (minoritas ganda) yang mengalami dekonstruksi struktural identitas dan eksistensi sebagai konsekuensi dari inisiatif pemerintah Cina 'Project Beauty'. Selain itu, kurangnya referensi mengenai terminologi Responsibility to Protect (R2P) yang berkaitan dengan kekerasan berbasis gender pada umumnya menjadi sangat penting untuk dikaji. Oleh karena itu, dengan menggunakan konteks perempuan Uyghur, artikel ini bertujuan untuk menyelidiki kekuatan Responsibility to Protect (R2P) dan untuk menelaah dan memvalidasi apakah pengabaian terhadap R2P berkorelasi dengan pelanggaran HAM berskala besar seperti yang ditunjukkan terhadap perempuan Uyghur. Kata kunci: Responsibility to Protect (R2P); Keamanan Gender; HAM; Perempuan Uyghur